Requirements and special considerations for drug trials with children across six jurisdictions: 2. Ethics review in the regulatory approval process - Stewart, Breanne; Lepola, Pirkko; Egger, Gunter F.; Ali, Fahimeda; Allen, Albert J.; Croker, Alysha K.; Davidson, Andrew J.; Dicks, Pamela; Faust, Saul N.; Green, Dionna; Hovinga, Collin; Klein, Agnes V.; et al. (Frontiers in Medicine, 2025)
BackgroundConducting clinical drug trials (CTs) with children presents several challenges. A major challenge is the need to enroll participants at multiple sites across different jurisdictions. Recruiting the required number of children within a reasonable timeframe requires the study to be reviewed by Research Ethics Boards (REB) or Institutional Review Boards (IRB) at multiple sites across various jurisdictions. This work, undertaken by the Working Group (WG) on International Collaborations at the European Network of Pediatric Research at the European Medicines Agency (Enpr-EMA) aims to describe the research ethics review requirements including any pediatric specific requirements, as well as current or upcoming changes across six jurisdictions – the European Union (EU), United Kingdom (UK), United States of America (USA), Canada, Japan, and Australia.MethodsAn open questionnaire developed by the WG and directed at both the Competent Authorities (CA) and the national pediatric clinical trial networks arranged by jurisdictions.ResultsA synopsis of the current regulatory requirements covers centralized versus independent review, comparisons between investigator initiated and industry sponsored clinical trials, timelines, review board members requirements and the consenting/assent process for clinical trial (CT) applications, application submission processes and application requirements for each of the six jurisdictions. It also describes changes currently or soon to be implemented in some jurisdictions.ConclusionThis environmental scan highlights the differences in ethics review for CTs in pediatric medicine development across six jurisdictions. While there is a growing trend for centralized ethics review, it is not universally permitted due to institutional, state/provincial, or national policies. Even where central review is allowed, local review may still be required for vulnerable populations like children. Harmonized and centralized ethics reviews offer advantages such as expert pediatric reviewers and efficient and consistent evaluations.